Emergent issues and vulnerability factors in temporary and intermediate shelters following the 2015 Nepal earthquake - Khazai, Bijan; Anhorn, Johannes (International journal of mass emergencies and disasters, 2016)
Analysis from University of Heidelberg, CEDIM, National Society for Earthquake Technology